The differential effect of NAT2 variant alleles permits refinement in phenotype inference and identifies a very slow acetylation genotype. - Jhon D Ruiz (Public Library of Science (PLoS), 2012)
Indirect evidences suggest that acetylation phenotype categories are heterogeneous and that subcategories, related to specific NAT2 variant alleles might exist. We analyzed the in vivo acetylation phenotype and genotype in 504 north-American subjects of Caucasian origin. The analyses of the SNPs rs1801280 and rs1799930 allowed the discrimination of five categories with different acetylation status within the study population. These categories are related to the distinct effect of NAT2 alleles on the acetylation status in vivo and to the occurrence of a gene-dose effect. These five phenotype categories, from higher to lower acetylation capacity, correspond to the genotypes NAT2*4/*4, NAT2*4/*5 or *4/*6, NAT2*5/*5, NAT2*5/*6 and NAT2*6/*6 (p ≤ 0.001 for all comparisons). The NAT2*6/*6 genotype correspond to a phenotype category of very-slow acetylators. The refinement in phenotype prediction may help to identify risks associated to phenotype subcategories, and warrants the re-analysis of previous studies that may have overlooked phenotype subcategory-specific risks.